PERTUMBUHAN STEK NILAM (Pogostemon cablin Benth) DENGAN PEMBERIAN PUPUK ORGANIK CAIR PADA KONSENTRASI YANG BERBEDA - Yuanita Yuanita (JURNAL AGRIMENT, 2017)
Patchouli nilam is a shrub which is widely cultivated and has a fairly high economic value of the benefits of this plant has a fairly good benefits compared with other shrubs.This study aims to measure the growth of plant height and the number of leaves on patchouli crops (Pogostemon cablin Benth) by giving different concentrations of organic fertilizer. This research was conducted for 2 months, covering preparation, execution and data retrieval. This research was carried out in the Samarinda State Agricultural Polyngogy area.The study consisted of 3 treatments and 15 replicates, the total patchouli cuttings total of 45 cuttings, the treatment consisted of P0 (Control / No treatment), P1 (10 ml Liquid Shrimp / Liquid Water), P2 (20 ml Liquid Fertilizer Shou / l water). The data taken consist of plant height and number of leaves on patchouli crops.The results showed that the treatment of P2 (20 ml of Feng Shou / l water liquid fertilizer) at the age of 2 MST, 4 MST and 6 MST highest growth was 23.55 cm, 27.23 cm and 30.87 cm. The highest number of leaf cuttings in P2 treatment can be seen at age 2 MST, 4 MST and 6 MST were 5.07 strands, 7.87 strands and 11.13 strands